THE ESSENCE OF FIXED ASSETS AS PROPERTY ACCOUNTING - T. Rogulenko; E. Egorova (Вестник университета, 2019)
The problem of determining the substance and content of the concept of fixed assets. The different point of view of Russian and foreign scientists to the economic nature of the category «fixed assets». Given the author's definition of «fixed assets».